2018
DOI: 10.1002/jsfa.9288
|View full text |Cite
|
Sign up to set email alerts
|

p‐Coumaric acid improves oxidative and osmosis stress responses in Caenorhabditis elegans

Abstract: Taken together, our results suggest that p-coumaric acid, an antioxidant agent, ameliorated oxidative and osmosis stresses in C. elegans. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
(86 reference statements)
1
32
0
Order By: Relevance
“…21,22 Yue Y. et al showed that p-CA reduces oxidative stress. 23 It has been demonstrated that p-CA has antifungal, antiviral, anti-melanogenic, antioxidant, and anti-infl ammatory effects. 24,18 Therefore, in this study, the effects of p-CA on oxidant/antioxidant balance in the R-IR model were investigated via biochemical measurements.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Yue Y. et al showed that p-CA reduces oxidative stress. 23 It has been demonstrated that p-CA has antifungal, antiviral, anti-melanogenic, antioxidant, and anti-infl ammatory effects. 24,18 Therefore, in this study, the effects of p-CA on oxidant/antioxidant balance in the R-IR model were investigated via biochemical measurements.…”
Section: Introductionmentioning
confidence: 99%
“…7 Thus, it is possible that butein's triglyceride-lowering effects via SKN-1-dependent pathway is due to SKN-1 activation by post-translational changes, which can occur with or without changes on skn-1 at transcript levels. 42,[44][45][46][47] However, it is yet not known whether butein induce SKN-1/Nrf activation by post-translational changes; thus, further studies are needed to determine the effects of butein on SKN-1/Nrf regulators, such as PMK-1 (the homolog of MAPK), and subsequently their contribution for the lipogenesis in C. elegans. 37,48 The butein's inhibitory effects on SCD homologs contribute to the reduced triglycerides in C. elegans, similar to the inhibitory effects on SCD by other polyphenols, such as fisetin, hesperidin, quercetin and resveratrol derivative in rats or C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…Catechin and p-coumaric acid have also anti-oxidant, anticancer, anti-bacterial effects are available [72,73] and their values were significantly lower than other phenols and control group (Fig. 3).…”
Section: Various Effects Of Phenolic Substancesmentioning
confidence: 95%